Inhibitory Effect of Morin Against Candida albicans Pathogenicity and Virulence Factor Production: An in vitro and in vivo Approaches - Abirami, Gurusamy; Alexpandi, Rajaiah; Durgadevi, Ravindran; Kannappan, Arunachalam; Veera Ravi, Arumugam (Frontiers in Microbiology, 2020)
Candida albicans is considered as an exclusive etiologic agent of candidiasis, a very common fungal infection in human. The expression of virulence factors is highly contributing to the pathogenicity of C. albicans. These factors include biofilm formation, yeast to hyphal transition, adhesins, aspartyl proteases, and phospholipases secretion. Moreover, resistance development is the critical issue for the therapeutic failure of antifungal agents against systemic candidiasis. To circumvent the resistance development, the present study investigated the virulence targeted therapeutic activity of the phyto-bioactive compound morin against C. albicans. Morin, a natural compound commonly found in medicinal plants and widely used in the pharmaceutical and cosmetic products/industries. The present study explicated the significant inhibitory potential of morin against the biofilm formation and other virulence factors production such as yeast-hyphal formation, phospholipase and exopolymeric substances in C. albicans. Further, qPCR analysis confirmed the downregulation of biofilm and virlence-related genes in C. albicans upon morin treatment, which is in correspondence with the in vitro bioassays. Further, the docking analysis revealed that morin shows strong affinity with Hwp-1 protein, which regulates the expression of biofilm as well as hyphal formation in C. albicans and, thereby, abolishes fungal pathogenicity. Moreover, the anti-infective potential of morin against C. albicans associated systemic candidiasis is confirmed through in vivo approach using biomedical model organism zebrafish (Danio rerio). The outcomes of in vivo study demonstrate that the morin treatment effectively rescues animals from C. albicans infections and extends their survival rate by inhibiting the internal colonization of C. albicans. Histopathology analysis revealed an extensive candidiasis-related pathognomonic changes in gills, intestine, and kidney of C. albicans infected animal, while no extensive abnormalities were observed in morin treated animals. The results evidenced that morin has the ability to protect the pathognomonic effect and histopathological lesions caused by C. albicans infection in zebrafish. Thus the present study suggests that the utilization of morin could act as a potent therapeutic medication for C. albicans instigated candidiasis.